RNA Structural Dynamics Modulate EGFR-TKI Resistance Through Controlling YRDC Translation in NSCLC Cells - Boyang Shi; Ke An; Yueqin Wang; Yuhan Fei; Caixia Guo; Qiangfeng Cliff Zhang; Yun-Gui Yang; Xin Tian; Quancheng Kan (Genomics, Proteomics & Bioinformatics, 2023)
Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) positively affect the initial control of non-small cell lung cancer (NSCLC). Rapidly acquired resistance to EGFR-TKIs is a major hurdle in successful treatment. However, the mechanisms that control the resistance of EGFR-TKIs remain largely unknown. RNA structures have widespread and crucial functions in many biological regulations; however, the functions of RNA structures in regulating cancer drug resistance remain unclear. Here, the psoralen analysis of RNA interactions and structures (PARIS) method is used to establish the higher-order RNA structure maps of EGFR-TKIs-resistant and -sensitive cells of NSCLC. Our results show that RNA structural regions are enriched in untranslated regions (UTRs) and correlate with translation efficiency (TE). Moreover, yrdC N6-threonylcarbamoyltransferase domain containing (YRDC) promotes resistance to EGFR-TKIs. RNA structure formation in YRDC 3′ UTR suppresses embryonic lethal abnormal vision-like 1 (ELAVL1) binding, leading to EGFR-TKI sensitivity by impairing YRDC translation. A potential therapeutic strategy for cancer treatment is provided using antisense oligonucleotide (ASO) to perturb the interaction between RNA and protein. Our study reveals an unprecedented mechanism through which the RNA structure switch modulates EGFR-TKI resistance by controlling YRDC mRNA translation in an ELAVL1-dependent manner.